2004
DOI: 10.1111/j.1523-1755.2004.00405.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic stretch-induced cPLA2 mediates ERK 1/2 signaling in rabbit proximal tubule cells

Abstract: PLA2 dependence for ERK 1/2 activation in response to cyclic stretch in proximal tubular epithelial cells was established in this report. In addition, these findings indicate cyclic stretch increased the tyrosine phosphorylation of the EGF receptor and c-Src and that c-Src acts upstream of the EGF receptor to mediate its phosphorylation, whereby both are critical for stretch- induced ERK 1/2 activation in rabbit proximal tubular cells. These observations documents for the first time a mechanism of mechanical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
67
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 41 publications
(31 reference statements)
8
67
0
Order By: Relevance
“…Stretching of kidney epithelial cells has been reported to cause ERK activation as well as proliferation, a crucial factor in cyst development (24,25). Alexander et al (25) recently demonstrated that cyclic stretch activates ERK in rabbit proximal tubule cells by releasing arachidonic acid through calcium channel activation followed by cPLA 2 phosphorylation, and subsequent events involved activation of c-Src and phosphorylation of EGF receptor, leading to ERK activation.…”
Section: Discussionmentioning
confidence: 99%
“…Stretching of kidney epithelial cells has been reported to cause ERK activation as well as proliferation, a crucial factor in cyst development (24,25). Alexander et al (25) recently demonstrated that cyclic stretch activates ERK in rabbit proximal tubule cells by releasing arachidonic acid through calcium channel activation followed by cPLA 2 phosphorylation, and subsequent events involved activation of c-Src and phosphorylation of EGF receptor, leading to ERK activation.…”
Section: Discussionmentioning
confidence: 99%
“…Persistence of the responses, however, in low external Ca 2ϩ argues against Ca 2ϩ entry as the initiating factor in the stretch-dependent responses of ICC-IM. Phospholipase A 2 (PLA 2 ), which liberates arachidonic acid, is mechanosensitive in some cells (46,47). Thus, it is possible that mechanotransduction coupling, linked through activation of PLA 2 , could be a previously unrecognized property of ICC-IM.…”
Section: Discussionmentioning
confidence: 99%
“…PLA 2 and Src kinase have also been implicated in the activation of TRPCmediated SOC and ROC activities (Hisatsune et al 2004;Bolotina and Csutora 2005;Vazquez et al 2004b). There is also evidence that indicates PLC may be MS (Brophy et al 1993), with some reports indicating that the mechanosensitivity depends upon Ca 2+ influx (Basavappa et al 1988;Matsumoto et al 1995;Ryan et al 2000;Ruwhof et al 2001;Alexander et al 2004) and others indicating independence of external Ca 2+ and Ca 2+ influx (Mitchell et al 1997;Rosales et al 1997;Moore et al 2002). In either case, the combined evidence indicates that mechanical forces transduced by MscCa and/or by MS enzymes may modulate the gating of all TRP channels.…”
Section: Discussionmentioning
confidence: 88%